Climate stress test of the Hungarian banking system - László Bokor (Magyar Nemzeti Bank, 2022)
This paper presents the pilot top-down climate stress test of the Hungarian banking system over the 2020-2050 horizon. The focus is on a core indicator of financial soundness, the ratio of non-performing loans. Three scenarios are considered with different grades of compliance with the Paris Agreement. Results show that, by 2050, the sectoral excess ratios of non-compliance are scattering from 0 to 19 percentage points.
Keywords: C51; C53; G21; Q54; 330; climate stress test; banking system; non-performing loans; sectoral granularity